EFFECTS OF FEEDING OLIVE LEAVES ON LACTATING PERFORMANCE OF AWASSI EWES - Belal S. Obeidat; Rana Ababneh (The Iraqi Journal of Agricultural science)
The current study aimed to study the effects of feeding olive leaves (OL) on milk yield, milk composition, body weight, and blood parameters of lactating Awassi ewes. Thirty-six newly lambed ewes and their single lambs were distributed at random and assigned to one of three diets: 0% OL (CON), 15% OL (OL15), and 30% OL (OL30) to replace the forage source in sheep's diets. The first seven days of the 56-day experiment were dedicated to adaptation, with the remaining 49 days dedicated to the collection of data. Dry matter (DM) intake was greater (p = 0.014) in the OL15 and OL30 groups compared with the CON group. Crude protein and ether extract intake was also the highest in the OL30 group (p=0.0172) followed by the OL15 group and was lowest for the CON group. The consumption of acid detergent fiber and neutral detergent fiber was higher (p < 0.0001) in CON compared to other groups. A decrease (p = 0.0510) in milk production cost was seen in the group-fed diets containing OL. There were no differences in initial body weight in ewes and lambs, while ewes fed on the CON lost more body weight compared with the OL30, while OL15 was intermediate. The average daily gain in lambs was greater in OL15 and OL30 compared to the CON group. In summary, substituting OL for wheat straw did not impact the lactation performance of ewes whilst it decreased the cost of producing milk and may benefit the livestock farmers.